Mystical elements in Ibn Al-Arabi's The Ringtones of Wisdom and Henry David Thoreau's Walden : a parallel study - Raihan bin Md Ghazali (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
The purpose of this thesis is to provide a parallel study between Ibn al-Arabi's Sufism with the mystical elements in Henry David Thoreau's Walden. The Sufi elements will be derived from Ibn al-Arabi's translated work entitled The Ringstones of Wisdom (Fusus al-Hikam; 2004). Sufism deals with the relationship between the individual and God. It is an attempt by man as a believer and worshipper to seek, find and be accepted by God. This quest is both physical and spiritual in nature. The individual passes different stages of self-examination and purgation before attaining the highest realm of spiritual fulfillment. So, in Sufism, life is a journey of self-discovery which leads to enlightenment. This is a form of spirituality which has affinities with the one explored by Henry David Thoreau in his book, Walden. In this study, Thoreau's work will be examined to discover parallels between elements of Sufism i.e. “Dream and Reality,” “He Who Knows Himself Knows His Lord,” and “Metaphysical Perplexity” with Thoreau's personal mysticism. These elements will be utilized to formulate the understanding of spiritual fulfillment and the self. This research will use relevant library sources which will include books, journals, encyclopedias, and relevant academic resources. The study is significant because it will add to the existing research done in this area. The research will also show some religious and spiritual elements that different schools of mysticism share in their examination of the individual's quest for moral enlightenment and self-fulfillment.